Periodontitis in a 65-year-old population: risk indicators and impact on oral health-related quality of life - Anne Thea Tveit Sødal; Rasa Skudutyte-Rysstad; My Tien Diep; Odd Carsten Koldsland; Lene Hystad Hove (BMC, 2022)
Abstract Aims The aims of the present study were to investigate socioeconomic and behavioral risk indicators for severe periodontitis in a 65-year-old Norwegian population, and to investigate how periodontitis impacts oral health-related quality of life. Material and methods A sample of 65-year-old residents in Oslo, born in 1954, was randomly selected for this study. The participants answered a questionnaire regarding country of birth, education, diabetes, smoking habits, dental attendance pattern, and tooth-brushing habits. In addition, oral health-related quality of life (OHRQoL) was assessed by the Oral Health Impact Profile-14 questionnaire (OHIP-14). Negative impact on OHRQoL was defined as responding "fairly often" or "very often" to at least one of the OHIP-14 items. The diagnosis of periodontitis was based on clinical and radiographic periodontal measurements and classified based on the consensus report from the 2017 World Workshop on the Classification of Periodontal and Peri-Implant Diseases and Conditions. Results Of 796 eligible participants, 460 individuals agreed to participate in the present study (response rate 58%). Seven participants were excluded from the analyses due to < 2 remaining teeth (n = 3) or missing questionnaire (n = 4), resulting in a study sample of 453 individuals (233 men and 220 women). An association was found between non-western country of birth, diabetes type 2, lower education, smoking, non-regular dental visits, and severe periodontitis (stage III or IV, n = 163) in bivariate analyses (Chi-square test). However, in the multiple logistic regression model, only non-western country of birth, diabetes type 2 and smoking (former and current), were associated with higher odds of severe periodontitis. The overall mean OHIP-14 total score was 3.6 (SD: 6.1). Participants with stage III or IV periodontitis reported a significantly higher OHIP-14 total score (mean: 4.7, SD: 7.4), indicating a lower OHRQoL, compared to non-periodontitis participants (mean: 2.9, SD: 4.9). Conclusions In the present study, non-western birth country, diabetes type 2, and smoking were found as significant risk indicators for severe periodontitis. Overall, results indicate a good OHRQoL among 65-year-olds in Oslo, however, a tendency of reduced OHRQoL with increasing severity of periodontitis was observed.